53rd AIAA Aerospace Sciences Meeting 2015
DOI: 10.2514/6.2015-0838
|View full text |Cite
|
Sign up to set email alerts
|

Linearized Navier-Stokes Simulations of the Spatial Stability of a Hypersonic Boundary-Layer on a Flared Cone

Abstract: The linear stability of a hypersonic boundary-layer is investigated for an almost sharp flared cone at Mach 6. Towards this end, a short-duration pulse through a small hole on the surface of the cone is utilized to excite a broad spectrum of frequencies and streamwise wave numbers in an axisymmetric domain. The flow conditions chosen are from the lowenthalpy experiments performed at the Boeing/AFOSR Mach-6 Quiet Tunnel (BAM6QT) at Purdue University. 1-3 In the present work, the newly developed version of the L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2018
2018

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 45 publications
0
1
0
Order By: Relevance
“…Over the course of 2014-2016, Salemi et al also modeled the 5-degree half-angle sharp cone configurations typical of the T5 tunnel at Caltech and investigated second mode synchronization with the slow acoustic spectrum. They investigated the effect of nonlinear disturbances, 33, 34 a flared cone geometry, 35 and high-temperature effects, 36 although the Prandtl number and ratio of specific heats were fixed in their real gas model. Overall, Salemi 37 concluded that the synchronization of mode F1 with the slow acoustic spectrum caused the emission of acoustic waves from the boundary layer into the free stream.…”
Section: Introductionmentioning
confidence: 99%
“…Over the course of 2014-2016, Salemi et al also modeled the 5-degree half-angle sharp cone configurations typical of the T5 tunnel at Caltech and investigated second mode synchronization with the slow acoustic spectrum. They investigated the effect of nonlinear disturbances, 33, 34 a flared cone geometry, 35 and high-temperature effects, 36 although the Prandtl number and ratio of specific heats were fixed in their real gas model. Overall, Salemi 37 concluded that the synchronization of mode F1 with the slow acoustic spectrum caused the emission of acoustic waves from the boundary layer into the free stream.…”
Section: Introductionmentioning
confidence: 99%